ICOR Analysis of Gorontalo Province - Kalzum r Jumiyanti; Wahyudin Hasan (Trunojoyo University of Madura, 2021)
Investment plays an important role as one of the regional economic drivers. Likewise, a various development success is determined by the quality of planning and accurate data. In general, the development planning is highly specified by an ability to provide financing sources scenario where one of which is investment as it is impactful in increasing economic growth rate and community welfare level intended.This research aims at determining ICOR value and investment needs estimate in Gorontalo Province and at determining sectors with a higher or lower capital productivity in Gorontalo Province. The research employs ICOR analysis to measure certain amount as a comparison between growth of capital (investment) with production. Through these indicators, the economic development planners can determine investments needed to increase the economy in compliance with the predetermined target. The research findings reveal that: 1) ICOR value from 2018 to 2020 is 0.29 on average and it is impacted by annual capital change (∆K) and output change (∆Y), 2) food industry sector in Gorontalo Province indicates a sufficiently low value of ICOR, and it is good due to the economic runs efficiently. Meanwhile, the chemistry and pharmacy industry sector shows massive capital productivity where a higher value of ICOR indicates capital-intensive technology use. Also, an ICOR-based sectoral investment projection signifies that the researchers set top three of future leading sectors in 2025 for investment projection in Gorontalo. They are food and plantation crops; trade and repair; and construction, 3) a stay-at-home policy urged by the government during the covid-19 pandemic has led to a significant change in community’s consumption style for basic needs such as water, electricity, gas, food, and medication.